Numerical investigations on influences of tunnel differential settlement on saturated poroelastic ground vibrations and lining forces induced by metro train - Shi, Li; He, Jie; Huang, Zhen; Sun, Honglei; Yuan, Zonghao (Soil dynamics and earthquake engineering (1984), 2022)
The influences of the tunnel settlement on vibrations of the saturated poroelastic ground and on the additional forces of the tunnel lining are investigated numerically in this paper. A three-dimensional finite element model incorporating the metro train, the tunnel lining and the saturated ground has been established. The ground settlement is introduced into the computational model by a specifically developed vehicle-rail interaction (VRI) element, through which the metro train can be dynamically coupled to the track. The ground is considered as a saturated poroelastic medium that is discretized by a self-developed saturated-soil element based on Biot's theory. Moreover, at truncation boundaries of the ground model, an absorbing boundary condition termed multi-transmitting formula (MTF) that is specially developed for the saturated soil element is applied to meet the far-filed radiation condition. With the inputs of ground settlement data from in-situ measurement, amplifications in the ground vibration and the lining forces have been quantitatively determined by comparing to the settlement-free case. It is found that the ground vibrational velocity and acceleration can reach 40–60 times the responses when there is no differential settlement of the tunnel; the dynamic internal forces including the axial force, the shear force and the bending moment of the tunnel lining can be 7–20 times higher than their static counterparts. •The ground vibrational velocity and acceleration can be as high as 40–60 times the responses when there is no differential settlement of the tunnel.•The differential settlement of the tunnel has negligible influence on the vibration amplification zone at the ground surface.•The differential settlement of the tunnel not only induce static internal forces to the lining structure, but also prompt the wheel/rail interaction and considerably amplify the dynamic internal forces of the lining.